Probiotics and clay detoxifier protected growth performance and intestinal barrier of lambs fed diet contaminated with aflatoxin B1 - WANG, J P; LIN, L; JIANG, Q R; HUANG, W L; LIU, N (The Indian Journal of Animal Sciences, 2019)
Probiotics or clay detoxifier can improve the intestinal health of monogastric animals fed diets contaminated with aflatoxin B1 (AFB1), but little is known in ruminants. This study aimed to investigate the effect of probiotics and clay detoxifier on the growth performance, enterotoxigenic bacteria, endotoxins and intestinal barrier of lambs fed diet contaminated with AFB1. Lambs (24) were randomly allocated into 4 groups with 6 replicates. Treatments included control, AFB1 (100 Î¼g/kg), probiotics (AFB1 + probiotics @ 3Ã—109 cfu/kg) and clay (AFB1 + clay @ 4.0 g/kg of feed). The trial lasted for 35 d. Results showed that AFB1 worsened body weight gain and feed conversion ratio, and these were recovered by probiotics and clay detoxifier supplementation. Also, AFB1 increased cecal counts of Clostridium perfringens, Salmonella, Escherichia coli and gram-negative bacteria, serum endotoxin and diamine oxidase, but decreased duodenal mRNA expressions of claudin-1, IgA inducing protein, junctional adhesion molecule 2 (JAM-2), joining chain of multimeric IgA and IgM (J-chain) and occludin. Probiotics ameliorated these negative effects, but for Clostridium perfringens and J-chain, whereas clay detoxifier only showed beneficial effects on Escherichia coli, gram-negative bacteria, endotoxins, claudin-1 and JAM-2. In addition, probiotics were more protective against enterotoxigenic bacteria and enterotoxic markers than clay detoxifier. The results suggest that the probiotics are capable of restoring growth performance and protecting intestinal barrier in lambs fed diet contaminated with AFB1.